Vertical Subperiosteal Mid-face-lift for Treatment of Malar Festoons - Hoenig, Johannes Franz (Springer-Verlag, 2011)
BACKGROUND: Malar mounds may be accentuated by chronic lid edema, with the development from malar edema to malar mounds and finally to malar festoons. Because standard techniques do not seem effective and not specifically proposed for the treatment of malar festoons, subperiosteal vertical upper-midface lift associated with lower blepharoplasty overcomes these shortcomings. METHODS: Twelve patients (3 males and 9 females, age = 47 ± 6 years) underwent video-assisted endoscopic subperiosteal vertical upper-midface lift (SUM-lift) in conjunction with a lower blepharoplasty between 2006 and 2007 for treatment of malar festoons. This includes simultaneous lower blepharoplasties and video-assisted transtemporal subperiosteal and sub-SMAS tissue release. RESULTS: All patients healed uneventfully without any major postoperative problems. The surgical outcome was evaluated according to the analysis of photographs obtained before and after surgery and the analysis of pre- and postoperative measurements. The technique we used (SUM-lift) achieved a significant rejuvenation of the midface and the malar festoons. CONCLUSION: Subperiosteal vertical midface lift resuspends and redrapes the facial network that originates at the level of the orbital rim. It seems to improve the permeability characteristics of the malar septum in the treatment of malar festoons and malar mounds by freeing the cheek tissue from underlying bone and redraping the malar septum. It is a reliable technique to improve malar mounds, palpebral bags, or festoons.